(untitled) (Boston, MA, 2007)
This supplementary reader is composed of both classic and contemporary articles that demonstrate the significant contributions that cultural anthropologists make; the emphasis is on the applicability of cultural anthropology to understanding and improving the present day human condition.
Keywords: Applied anthropology,Anthropology,Ứng dụng nhân học,Nhân loại học